Effect of Cutting Speed on Surface Roughness AS-Scrapper ST37 Using Coated Carbide Tool - Fransnazoan Sitorus; Dejoi Irfian Situngkir; A Hafizh Saifullah; Nuzuli Fitriadi (Jurnal Inotera, 2024)
In the lathe machining process, especially surface roughness, are greatly influenced by the cutting angle of the tool, feeding speed, cutting speed and depth of cut. Research purposes is to determine the effect of cutting conditions, namely cutting speed (v) and cutting depth (a) on the level of surface roughness (Ra) on the ST37 As Scrapper material using quantitative research methods that focus on numeric or numbers in a study. The research results obtained a value of Ra ⃗= 6.063 µm at optimum cutting conditions varying a= 1 mm, v= 62 m/min, f= 0.05 mm, tc= 5.29 min.